THEORTICAL FOUNDATIONS OF WORKPLACE DIGNITY (Conferencea, 2023)
Extant research on dignity at work has revealed conditions that contribute to indignity, employees’ responses to dignity threats, and ways in which employees’ inherent dignity is undermined. But while dignity – and specifically indignity – is theorized as a phenomenon subjectively experienced and judged by individuals, little research has privileged workers’ own perspectives. In this study, working adults reveal how they personally experience and understand meanings of dignity at work. I describe three core components of workplace dignity and the communicative exchanges through which dignity desires commonly are affirmed or denied: inherent dignity as recognized by respectful interaction, earned dignity as recognized by messages of competence and contribution, and remediated dignity as recognized by social interactions and organizational practices that conceal the instrumental and unequal nature of work. Based on theoretical insights drawn from examining the relationships between these components, I argue that workplace dignity is a phenomenon theoretically distinct from human dignity.